Reliability of Screening Methods to Diagnose Oral Dryness and Evaluate Saliva Secretion - Takaharu Goto; Takahiro Kishimoto; Yuki Iwawaki; Keiko Fujimoto; Yuichi Ishida; Megumi Watanabe; Kan Nagao; Tetsuo Ichikawa (MDPI AG, 2020)
In this study, we evaluated the reliability and reproducibility of widely implemented salivary flow rate and oral dryness tests. In experiment 1, twenty young and healthy Japanese participants volunteered to participate. For each participant, the oral moisture (OM) level, unstimulated whole saliva volume (U-WSV), and stimulated whole saliva volume (S-WSV) were measured at the same time on two separate days. In experiment 2, twenty-seven patients who were over 65 years of age volunteered to participate. The OM level and U-WSV were measured at the same time on two separate days. In Experiment 1, the intra-class correlation coefficients (ICCs) corresponding to the S-WSV, U-WSV, and OM level were 0.23, 0.28, and 0.16, respectively, for the young participants. In Experiment 2, the ICCs corresponding to the U-WSV/spitting and OM level were 0.83 and 0.12, respectively, for the older participants. The results of Bland-Altman analysis confirmed the absence of systematic error, with the exception of the OM level results in Experiment 2, which indicated systematic bias. In conclusion, we believe that there is currently no consistent and reliable screening test for assessing salivary flow rate and oral dryness, although the spitting test was determined to be highly reliable.